The aid of microsurgical instruments in nasolabial cyst enucleation. A report of two cases with critical review of the therapeutic approach. Issue 1 (25th January 2023) - Tilaveridis, Ioannis; Venetis, Gregory; Tatsis, Dimitris; Kalaitsidou, Ioanna; Zouloumis, Lambros
Abstract: Nasolabial cysts are rare non-odontogenic cysts related to epithelial remnants of the nasolacrimal duct, slowly enlarging and provoking extraoral swelling in the nasolabial fold with obstruction of the naris. Two patients of large unilateral nasolabial cysts are reported, appearing as cosmetically unappealing distention of the nasolabial fold. Diagnosis is based on clinical characteristics. Computed tomography imaging reveals the dimensions of the cyst, the correlation to the nasal cavity and might depict a depression on the labial surface of the maxilla. Intraoral surgical enucleation of the cystic wall or nasal marsupialization is the main treatment modalities. However, both procedures are related to a small percentage of recurrence. Microsurgical instruments were used to dissect the cystic wall from the nasal mucosa. The aim of this paper is to stress the implementation of microsurgical instruments to separate the cystic wall of the nasolabial cyst from the thin and friable nasal mucosa to avoid recurrence.